2021
DOI: 10.1097/j.jcrs.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Anterior, posterior, and nonkeratometric contributions to refractive astigmatism in pseudophakes

Abstract: Purpose: To investigate the relationship between measured anterior (ACA) and posterior (PCA) keratometric astigmatism and postoperative refractive astigmatism (RA) and to quantify noncorneal astigmatism (NCA) contributions to RA. Setting: Penn State College of Medicine, Hershey, Pennsylvania, USA. Design: Retrospective consecutive case series. Methods: Consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“… 37–39 Several studies have since used rotating Scheimpflug imaging and dual Scheimpflug and Placido disk imaging to demonstrated that PCA has an average magnitude of approximately 0.24–0.42 D and is vertically oriented in the majority of eyes, particularly in patients with WTR anterior corneal astigmatism. 7 , 9 , 12 , 20 , 22 , 26 , 39–43 LaHood et al 14 measured PCA using the recently released IOLM with SS-OCT and telecentric keratometry and found that PCA ranged from 0 to 1.21 D with an average magnitude of 0.24 D. Similar to Scheimpflug and Purkinje imaging, IOLM measured a vertically oriented steep axis of the posterior cornea in 73% of eyes and PCA was found to be significantly greater in WTR eyes compared to ATR eyes. 14 In the present study, an average PCA of 0.24 ± 0.15 D (ranging from 0 to 0.67 D) was measured using IOLM for all eyes and higher PCA was observed in WTR eyes compared to ATR eyes, which aligns with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 37–39 Several studies have since used rotating Scheimpflug imaging and dual Scheimpflug and Placido disk imaging to demonstrated that PCA has an average magnitude of approximately 0.24–0.42 D and is vertically oriented in the majority of eyes, particularly in patients with WTR anterior corneal astigmatism. 7 , 9 , 12 , 20 , 22 , 26 , 39–43 LaHood et al 14 measured PCA using the recently released IOLM with SS-OCT and telecentric keratometry and found that PCA ranged from 0 to 1.21 D with an average magnitude of 0.24 D. Similar to Scheimpflug and Purkinje imaging, IOLM measured a vertically oriented steep axis of the posterior cornea in 73% of eyes and PCA was found to be significantly greater in WTR eyes compared to ATR eyes. 14 In the present study, an average PCA of 0.24 ± 0.15 D (ranging from 0 to 0.67 D) was measured using IOLM for all eyes and higher PCA was observed in WTR eyes compared to ATR eyes, which aligns with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…All these variables typically have little influence on the total refractive astigmatism in pseudophakia, but they may become relevant when the corneal contribution is very low [ 21 23 ]. Moreover, the total amount of the pseudophakic refractive astigmatism cannot be explained by the sole refractive assessment of the anterior segment, even if it is conducted in detail [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude and meridian of the anterior corneal astigmatism were also measured using TONOREF I and II. Furthermore, ocular residual astigmatism which was defined as the difference between manifest refractive astigmatism and anterior corneal astigmatism by Alpins was calculated [ 24 , 25 ]. …”
Section: Methodsmentioning
confidence: 99%